The Floor of the Sea / Maurice Ewing and the Search to Understand the Earth - Wertenbaker William; Little, Brown and Company (1974)
Foreword, The Floor of the Sea, The Chief Scientist Dreamed of Cervantes, Lifeless Depths and Living Fossils and Lost Continents, A Scene the Most Rugged and Grant and Imposing, Torrey Cliff, That Man is Taking Too Many Cores, I Wasn't Lonely a Bit, Rift and Ridge, Diluvialists and Other Fauna, To Gondwanaland, Eltanin-19, Global Tectonics, Bibliography and Works Consulted, Picture Credits, Index.